2013
DOI: 10.3758/s13423-013-0527-8
|View full text |Cite
|
Sign up to set email alerts
|

Aging and the use of interword spaces during reading: Evidence from eye movements

Abstract: An eye movement experiment assessed the performance of young (18-30 years) and older (65+ years) adult readers when sentences contained conventional inter-word spaces, inter-word spaces were removed, or inter-word spaces were replaced by a non-linguistic symbol. The replacement symbol was either a closed square (■) that provided a salient (low spatial-frequency) cue to word boundaries, or an open square (□) that provided a less salient cue and included features (vertical and horizontal lines) similar to those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
69
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(100 citation statements)
references
References 25 publications
25
69
6
Order By: Relevance
“…These findings are important in two respects. First, they suggests that age differences in word frequency effects in Chinese reading may be similar to those observed for alphabetic languages (Kliegl et al, 2004;McGowan et al, 2014;Rayner et al, 2006Rayner et al, , 2013Whitford & Titone, 2017), and in line with the predictions of models of eye movement control (Engbert et al, 2005;Reichle et al, 2003). Second, the findings suggest that the aging effects we observed arise from a small proportion of long fixation times on words.…”
Section: Discussionsupporting
confidence: 85%
“…These findings are important in two respects. First, they suggests that age differences in word frequency effects in Chinese reading may be similar to those observed for alphabetic languages (Kliegl et al, 2004;McGowan et al, 2014;Rayner et al, 2006Rayner et al, , 2013Whitford & Titone, 2017), and in line with the predictions of models of eye movement control (Engbert et al, 2005;Reichle et al, 2003). Second, the findings suggest that the aging effects we observed arise from a small proportion of long fixation times on words.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, older adults often show larger effects of word frequency, due to a disproportionate increase in fixation times for lower frequency words, consistent with older readers having greater difficulty identifying words (e.g., McGowan et al, 2014;Rayner et al, 2006Rayner et al, , 2013.…”
Section: Eye Movements and Ageing In Chinese Readingmentioning
confidence: 81%
“…In addition, McGowan et al (2014;see also Rayner et al, 2013) compared the reading performance of young and older adults when sentences contained conventional interword spaces and when interword spaces were removed or replaced by nonlinguistic symbols. When interword spaces were absent, the older adults read more cautiously, presumably to compensate for the greater difficulty they had segmenting unspaced text.…”
Section: Eye Movements and Ageing In Chinese Readingmentioning
confidence: 99%
“…Ultimately, research on the effects of inter-word spacing and word boundary information has demonstrated that space information is extracted early in the reading process (Pollatsek & Rayner, 1982) and plays a major role in helping readers identify words and direct eye movements (Perea & Acha, 2009;Rayner et al, 1998). These conclusions are based on the finding that readers experience difficulty reading text where inter-word spaces have been filled in with another symbol (Epelboim, Booth, Ashkenazy, Taleghani, & Steinman, 1997;Johnson & Eisler, 2012;Malt & Seamon, 1978;McConkie & Rayner, 1975;McGowan, White, Jordan, & Paterson, 2014;Morris et al, 1990;Pollatsek & Rayner, 1982;Rayner et al, 1998;Spragins, Lefton, & Fischer, 1976) or word boundaries have been removed altogether (Drieghe, Fitzsimmons, & Liversedge, 2017;Johnson & Eisler, 2012;Paterson & Jordan, 2010;Perea & Acha, 2009;Rayner et al, 1998;Spragins et al, 1976). Studies that have explored the effects of increasing the inter-word spacing have shown mixed effects.…”
mentioning
confidence: 99%